ANALISIS PENGARUH MOBILE BANKING DAN PERUBAHAN NILAI AKTIVA TETAP TERHADAP KINERJA KEUANGAN BANK KONVENSIONAL DI INDONESIA STUDI EMPIRIS PADA BANK UMUM KONVENSIONAL - Reghina Syalsa Jauhari; Mokhamad Anwar (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the effect of the number of mobile banking users, the value of mobile banking transactions, and changes in fixed asset values on the financial performance of conventional banks in Indonesia as measured by Return on Assets (ROA) and Return on Equity (ROE), with Bank Size as a control variable. This study uses secondary data obtained from bank annual reports as well as publications from the Financial Services Authority and Bank Indonesia during the 2017–2024 period. The sample was determined using purposive sampling techniques and analyzed using panel data regression. The results indicate that the number of mobile banking users does not significantly affect ROA and ROE. The value of mobile banking transactions does not significantly affect ROA, but has a positive and significant effect on ROE. Meanwhile, changes in fixed asset values do not significantly affect ROA and ROE. Bank Size has a positive and significant effect on ROA and ROE. Simultaneously, all independent variables significantly affect the financial performance of conventional banks in Indonesia. The findings indicate that optimizing mobile banking services and managing technology investment effectively can become a strategy to improve sustainable bank financial performance. Keywords: Mobile Banking, Mobile Banking Transaction Value, Fixed Assets, Bank Financial Performance